2017
DOI: 10.3390/w9110898
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Predictive Tool to Support Environmentally Sustainable Management in Port Basins

Abstract: According to the Water Framework Directive, harbours that are classified as heavily modified water bodies must either reach or maintain good ecological potential. Moreover, following the marine spatial planning principles, the effects of port structure changes on water quality must also be considered. To support the sustainable management of harbour waters, we calculated flushing time (FT) through the use of a numerical model within the Civitavecchia port under different scenarios. To assess the effects of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Saengsupavanich [8] showed that there was limited water circulation within the Chiang Saen Commercial Port of Thailand, to show that there was unsatisfactory water quality within the port basin. Numerically, Bonamano et al [28], using the inner part of Civitavecchia Port, Italy, as an example, showed that deterioration in water quality and high concentrations of heavy metals are possible with a decrease in the flushing time.…”
Section: Water Quality Within the Port Basinmentioning
confidence: 99%
“…Saengsupavanich [8] showed that there was limited water circulation within the Chiang Saen Commercial Port of Thailand, to show that there was unsatisfactory water quality within the port basin. Numerically, Bonamano et al [28], using the inner part of Civitavecchia Port, Italy, as an example, showed that deterioration in water quality and high concentrations of heavy metals are possible with a decrease in the flushing time.…”
Section: Water Quality Within the Port Basinmentioning
confidence: 99%
“…The port includes many kilometers of piers and may host big cruise ships. The Laboratory of Experimental Oceanology and Marine Ecology (LOSEM), in collaboration with the Port Authority of Civitavecchia, has recently developed an integrated monitoring system for the study of water quality, with the aim of assessing the possible impact of the continuously expanding port activities on the marine ecosystem (Bonamano et al, 2016;Bonamano et al, 2017;ZappalĂ  et al, 2016).…”
Section: Port Of Civitavecchiamentioning
confidence: 99%
“…The LOSEM (Laboratory of Experimental Oceanology and Marine Ecology) developed the C-CEMS (Civitavecchia Coastal Environment Monitoring System) that allows to analyse the potential impacts of the anthropogenic sources in marine environment of Civitavecchia coastal zone [20]. In detail, many studies concerning the bacterial dispersion in bathing areas [21]- [24], the effects of dredging activities on P. oceanica meadows and soft bottom benthic community [25] and water quality within Civitavecchia port [26], [27] have been carried out. Moreover, new low cost environmental monitoring technologies have been developed by the LOSEM and tested in the study area [28].…”
Section: The Study Areamentioning
confidence: 99%